Hubungan Tingkat Pengetahuan dengan Tingkat Kepatuhan Radioterapi pada Pasien Kanker di Instalasi Radioterapi RSUD Abdul Wahab Sjahranie Samarinda - Ananda Purnama Mazna (Jurnal Ilmu Kesehatan dan Kesehatan, 2020)
Cancer is a disease characterized by abnormal cell growth outside the usual boundary then attacks the adjacent body and can spreads to other organs. Cancer treatment can be done with several therapies according to indications, one of them is radiotherapy. One of succession factor in the radiotherapy treatment for cancer is having good knowledge. Treatment adherence is very important to get optimal results such as healing or improving quality of life. The aim of this research was to determine the relationship between radiotherapy knowledge with radiotherapy adherence in undergoing radiotherapy cancer patients at General Hospital of Abdul Wahab Sjahranie Samarinda . This research was an observational analytic design with cross-sectional approach. Data retrieval was done at the Radiotherapy Installation at General Hospital of Abdul Wahab Sjahranie Samarinda from March to April 2019 by using a purposive sampling technique. The results showed that there were 50 samples who met the inclusion and exclusion criteria with details of patients who had good knowledge was 33 people, sufficient knowledge was 15 people, bad knowledge was 2 people and obey patients was 46 people and disobey patients was 4 people. Data analysis using Fisher's test obtained the value of p = 0.157 so it can be concluded that there was no relationship between radiotherapy knowledge and radiotherapy adherence in cancer patients at Radiotherapy Installation at General